2022
DOI: 10.1001/jama.2022.9930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graded Sensorimotor Retraining on Pain Intensity in Patients With Chronic Low Back Pain

Abstract: IMPORTANCEThe effects of altered neural processing, defined as altering neural networks responsible for perceptions of pain and function, on chronic pain remains unclear.OBJECTIVE To estimate the effect of a graded sensorimotor retraining intervention (RESOLVE) on pain intensity in people with chronic low back pain. DESIGN, SETTING, AND PARTICIPANTSThis parallel, 2-group, randomized clinical trial recruited participants with chronic (>3 months) nonspecific low back pain from primary care and community settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
39
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 25 publications
(48 reference statements)
2
39
0
Order By: Relevance
“…Low back pain is a leading cause of disability worldwide. [1][2][3] The lifetime prevalence of low back pain is about 40% with 5-10% of acute pain developing into chronic low back pain (cLBP), defined as having low back pain for longer than 3 months. 4 About 85% of adults with cLBP have non-specific low back pain, where an underlying pathology or a nociceptive contributor cannot yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Low back pain is a leading cause of disability worldwide. [1][2][3] The lifetime prevalence of low back pain is about 40% with 5-10% of acute pain developing into chronic low back pain (cLBP), defined as having low back pain for longer than 3 months. 4 About 85% of adults with cLBP have non-specific low back pain, where an underlying pathology or a nociceptive contributor cannot yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study 1 reported that patients with low-risk stage II and T3N0M0 cancer who received IMRT alone had the same oncologic outcomes but better long-term quality of life than those who received concurrent chemoradiotherapy. We have 3 concerns about the definition of the truly low-risk NPC.…”
mentioning
confidence: 98%
“…The mean survival time provides a global measure and is more statistically efficient and clinically interpretable than the hazard ratio. 3 Using reconstructed individual patientlevel data 4 from Figure 2, A and B, 1 the difference (IMRT alone minus concurrent chemoradiotherapy) in 5-year mean failurefree survival was −1.28 months (95% CI, −3.87 to 1.32 months) and for overall survival, it was −0.71 months (95% CI, −1.81 to 0.40 months). These narrow confidence intervals enhance the decision-making process for treatment selection.…”
mentioning
confidence: 99%
“…Additionally, the safety profiles between the 2 groups were reported separately from efficacy comparisons, and the concurrent chemoradiotherapy group had substantially higher grade 3/4 acute and late adverse events compared with IMRT alone (Table 2 in the article). 1 Use of separate summary measures to assess the overall treatment effect is suboptimal because it does not incorporate the relationship between efficacy and toxicity at the individual patient level. An alternative is to construct a composite end point (net clinical benefit) 5 from efficacy and safety outcomes to compare the 2 treatments, which may show that IMRT is superior to concurrent chemoradiotherapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation